KDM5A demethylase: Erasing histone modifications to promote repair of DNA breaks - Price, Brendan D. (J Cell Biol, 2017)
Repairing DNA breaks within the complexity of the cell chromatin is challenging. In this issue, Gong et al. (2017. J. Cell Biol. https://doi.org/10.1083/jcb.201611135) identify the histone demethylase KDM5A as a critical editor of the cells’ “histone code” that is required to recruit DNA repair complexes to DNA breaks.